Development of remotely operated vehicle (ROV) for underwater exploration - Azizie, Asmawi (2009)
This thesis deals with the development of vehicle design, fabrication and testing of the micro class tethered remotely operated vehicle (ROV) for underwater exploration. It will emphasize on the development of tri-thruster ROV. This will be a new type of design where the ROV will have two motors mounted at the front. Its layout is very different from other conventional ROV which have two horizontal motors mounted at the rear. The development accentuate on mechanical approach. The ROV developed will have hydrodynamic features add to it. The prototype is modeled using SOLIDWORKSTM and the further analysis of the model was done using COSMOSFloWorksTM. The quantitative analyses done has determined limiting factor for the ROV as it is desired to be operational in both sea and fresh water for a limited depth. For the fabrication purpose, this project will proceed with PVC pipe as its main component for frame. In methodological section, objective of material selection was to reduce fabrication cost without reducing the performance. The type of onboard control method used simple circuit of double pole double throw (DPDT). Simple circuit were chosen as it is easier to troubleshot and provide more reliability in executing motion compare to complex coding. From COSMOS analysis, the hydrodynamic cover performs very well in decreasing the drag force of developed vehicle. Guided by preliminary result and initial specification, a handmade fabrication will be done to create a prototype to show how this innovative ROV behave underwater, how its drive system response, how the control is functioned and how the motions are perform. The real time testing then runs and the testing bed preferred were surrounding area and control environment. The result was than recorded in video and examination done base on the recorded motion. From real time analysis, the hydrodynamic cover effectively smoothen the prototype motion at underwater and within water surface. The fabricated model can submerge, resurface, move forward and reverse, rotate to left and right. The result of this development will be significantly improved the existing design of ROV and pioneering the future development of remotely operated vehicle for underwater exploration. The fabricated model has installed camera and the first to be equipped with oblique hydrodynamic cover and frontal thruster layout. The development in phrase can be concluded as an innovation of design and invention of layout.